Parents attending to nurse visits and birth age contribute to infant development: A study about the determinants of infant development. (July 2018) - Soares, Hélia; Barbieri-Figueiredo, Maria; Pereira, Sandra; Silva, Manuela; Fuertes, Marina
Abstract: Life experiences and parenting play an important role in infant development. To prevent developmental risks and support parents in their educational role, it is important to identify the determinants of infant development. In this study, we investigate the association between child, maternal, family and social variables, and infant development, as well as we investigate the determinants of infant development. A sample of 86 healthy infants and their mothers participated in this study. At 11-months, infant development was assessed with Schedule of Growing Skills II (SGSII). To assess mother-infant quality of interaction, the dyads were observed in free play at 12-months using CARE-Index. Maternal sensitivity and infant cooperative behavior were correlated with SGSII global scores and sub-scales. Infant development was associated with maternal years of education, number of siblings, birth weight or risks in pregnancy. Number of nurse visits attended by parents during the infant first year and birth age were determinants of infant development. Highlights: Maternal sensitivity and infant cooperative behavior are correlated with Schedule of Growing Skills II global scores. Infant development is associated with maternal education, number of siblings, birth weight and risks in pregnancy. Nurse visits attended by parents during infant's first year and gestational age were determinants of infant development.